PENGARUH PEMUPUKAN DAN JARAK TANAM TERHADAP PERTUMBUHAN TANAMAN SERAI WANGI (Cymbopogon citratus) - Barba N.H. Sopacua (Politeknik Pembangunan Pertanian Manokwari, 2016)
Lemongrass plant is an herb that is relatively common planted in the yard. Lemongrass plant has more than one species, one of which is citronella (Cymbopogon sp.). Plant citronella essential oil is cultivated to take because it has a fairly high economic value. Price per kg to Rp. 150.000, - used as raw materials of perfumes and medicines. Citronella plant production in the period of five years (2009 - 2013) continued to increase, from 1700 tonnes / ha to 2,600 tonnes / ha. While citronella plant acreage has declined in the last five years (2009 - 2013) is from 20,000 ha to 19,000 ha. In the province of West Papua, until now there is no comprehensive data on production and planting area citronella (CBS, 2014). Experimental design used was RAKL (Random Group Complete). The results showed that the use of organic fertilizer to yield significant results on plant growth citronella